STUDI KUALITATIF DAMPAK UJI KOMPETENSI DOKTER INDONESIA TERHADAP PEMBELAJARAN PADA MAHASISWA KEDOKTERAN - , Marindra Firmansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. The medical education institution should have two important characteristics as the institutionâs consideration, the first is about the importance of using the right assessment as a measuring instrument and the role of curriculum in producing good quality graduates. UKDI is only one exit to be a doctor that will certainly have varied impact on students from the expected and unexpected. Objectives. The purpose of this study was to determine the impact on studentâs UKDI learning, on which will follow UKDI, related to the allocation of time for study, the number of hours of study, the distribution of learning, the selection of learning resources and learning materials selection. Methods. The research method on this study is qualitative study that uses Focus Group Discussion to get the data. The number of participants is 61 students divided into 6 groups. The groups of students is at the Faculty of Medicine with the accreditation of A, B and C respectively - each of the public and private colleges. Results. The results of qualitative analysis portrayed that UKDI has an impact on the student learning. The impact of learning that occurs associated with two things, the first is relate to the quality of student learning and the second related to student metacognitive regulation. The general quality of the studentâs learning that occurs in facing UKDI is still low, which is learning by memorizing. For metacognitive regulation is relate to the allocation, the number and distribution of learning, the selection of learning materials, the selection of learning resources, the selection of a place of learning, learning strategies, learning to maintain consistency, and monitoring the process of learning and improvement. Conclusion. UKDI have an impact on the learning of medical students, both in the quality of learning and metacognitive regulation.